2010
DOI: 10.1051/0004-6361/201015094
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the light variability of the Ap starε Ursae Majoris

Abstract: Aims. We simulate the light variability of the Ap star ε UMa using the observed surface distributions of Fe, Cr, Ca, Mn, Mg, Sr, and Ti obtained with the help of the Doppler imaging technique. Methods. Using all photometric data available, we specified light variations of ε UMa modulated by its rotation from far UV to IR. We employed the LLmodels stellar model atmosphere code to predict the light variability in different photometric systems. Results. The rotational period of ε UMa is refined to 5.d 088631(18).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 42 publications
(107 reference statements)
5
57
0
Order By: Relevance
“…The theoretical light curves can be predicted using model atmospheres calculated with actual abundances from abundance maps of individual stars. A comparison of such theoretical light curves with observed ones supports the current picture of the light variability of CP stars (Krtička et al 2009(Krtička et al , 2012Shulyak et al 2010). This approach cannot be used for rotationally variable normal A stars because the expected abundance and line profile variations are prohibitively small for abundance mapping.…”
Section: Introductionsupporting
confidence: 79%
“…The theoretical light curves can be predicted using model atmospheres calculated with actual abundances from abundance maps of individual stars. A comparison of such theoretical light curves with observed ones supports the current picture of the light variability of CP stars (Krtička et al 2009(Krtička et al , 2012Shulyak et al 2010). This approach cannot be used for rotationally variable normal A stars because the expected abundance and line profile variations are prohibitively small for abundance mapping.…”
Section: Introductionsupporting
confidence: 79%
“…However, as can be seen from e.g. Shulyak et al (2010a) and Krtička et al (2012), the amplitude of this variability is rather small to influence the derived effective temperatures much. For instance, using Adelman's spectrophotometric catalog, we find that the relative characteristic correction to the effective temperatures due to flux variability is only a few ten K's for all three target stars.…”
Section: Observationsmentioning
confidence: 94%
“…CPs are stars in the upper part of the main-sequence with B or A spectral types, which present an inhomogeneous surface distribution of chemical elements and yield near-sinusoidal light curves as a result of stellar rotation. Variability is often attributed to strong and stable magnetic fields (e.g., Lüftinger et al 2010;Krtička et al 2012), although cases with weak magnetic fields have been reported as well (e.g., Krtička et al 2009;Shulyak et al 2010). The amplitude of the light variations decreases with increasing wavelength (Catalano et al 1991).…”
Section: Candidate Rotating Variables/overcontact Binariesmentioning
confidence: 99%